PENGARUH TEKANAN KLIEN DAN AUDIT TENURE TERHADAP KUALITAS AUDIT DENGAN ETIKA AUDITOR SEBAGAI VARIABEL PEMODERASI - Sasmita, Rezza Dian; Widaryanti, Widaryanti (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2022)
This study aims to determine whether client pressure and audit tenure have an effect on audit quality and auditor ethics as a moderator. The population in this study is the Public Accounting Firm in Semarang. Sampling was carried out using the census method and the number of samples was 53 respondents. The type of data used is primary data. This study uses a questionnaire in collecting data. The test techniques used are validity test, reliability test, classic assumption test including normality test, multicollinearity test and heteroscedasticity test. Hypothesis testing in this study used the interaction moderation test (MRA) with SPSS version 26. The results of this study indicate that Client Pressure has a positive and significant effect on Audit Quality. While the Tenure Audit has no positive and significant effect on Audit Quality. Auditor Ethics is able to moderate the effect of Client Pressure on Audit Quality. Meanwhile, the Auditor Ethics is not able to moderate the influence of the Tenure Audit on Audit Quality.Keywords: Client Pressure, Audit Tenure, Audit Quality, Auditor Ethics